SCIENTIFIC/OTHER WITNESS APPEARANCE REQUIREMENTS - AVEDON, DIANA (Tufts Archival Research Center, 2007)
Letter from Diane Avedon to tobacco industry officials regarding witness appearance requirements. Contains schedule for media tours, public affairs workplace/legal expert tours and social costs tours. Emphasizes that legislative hearings take precedence over media tours.